Reactive oxygen species-responsive dendritic cell-derived exosomes for rheumatoid arthritis. (1st July 2021) - Lee, Eun Sook; Sul, Jae Hoon; Shin, Jung Min; Shin, Sol; Lee, Jae Ah; Kim, Hark Kyun; Cho, Yongeun; Ko, Hyewon; Son, Soyoung; Lee, Jeongmi; Park, Sunyoung; Jo, Dong-Gyu; et al.
Abstract: Although tolerogenic dendritic cell-derived exosomes (TolDex) have emerged as promising therapeutics for rheumatoid arthritis (RA), their clinical applications have been hampered by their poor in vivo disposition after systemic administration. Herein, we report the development of stimuli-responsive TolDex that induces lesion-specific immunoregulation in RA. Responsiveness to reactive oxygen species (ROS), a physiological stimulus in the RA microenvironment, was conferred on TolDex by introducing a thioketal (TK) linker-embedded poly(ethylene glycol) (PEG) on TolDex surface via hydrophobic insertion. The detachment of PEG following overproduction of ROS facilitates the cellular uptake of ROS-responsive TolDex (TKDex) into activated immune cells. Notably, TolDex and TKDex downregulated CD40 in mature dendritic cells (mDCs) and regulated secretion of pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α and interleukin-6 (IL-6) at the cellular level. In the collagen-induced arthritis (CIA) mouse model, PEG prolonged the blood circulation of TKDex following intravenous administration and enhanced their accumulation in the joints. In addition, TKDex decreased IL-6, increased transforming growth factor-β, and induced the CD4 + CD25 + Foxp3 + regulatory T cells in CIA mice. Overall, ROS-responsive TolDex might have potential as therapeutic agents for RA. Statement of significance: Tolerogenic dendritic cell-derived exosomes (TolDex) are emerging immunoregulators of autoimmune diseases, including rheumatoid arthritis (RA). However, their lack of long-term stability and low targetability are still challenging. To overcome these issues, we developed reactive oxygen species (ROS)-responsive TolDex (TKDex) by incorporating the ROS-sensitive functional group-embedded poly(ethylene glycol) linker into the exosomal membrane of TolDex. Surface-engineered TKDex were internalized in mature DCs because of high ROS-sensitivity and enhanced accumulation in the inflamed joint in vivo . Further, for the first time, we investigated the potential mechanism of action of TolDex relevant to CD40 downregulation and attenuation of tumor necrosis factor (TNF)-α secretion. Our strategy highlighted the promising nanotherapeutic effects of stimuli-sensitive TolDex, which induces immunoregulation. Graphical abstract: Image, graphical abstract